2007
DOI: 10.1509/jmkg.71.4.195
|View full text |Cite
|
Sign up to set email alerts
|

The Performance Implications of Designing Multiple Channels to Fit with Strategy and Environment

Abstract: Applying a configuration-theoretic approach to study multiple channels, the authors hypothesize that multiple-channel systems make their greatest contributions to firm performance when their structures are properly aligned with their firms' business-level strategies and with environmental conditions. A conceptual model incorporating these variables is supported in an empirical study of responses from executives at 291 electronic component manufacturers. The results confirm the existence of two theoretically id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
131
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 91 publications
3
131
0
3
Order By: Relevance
“…Using the configuration-theoretic approach, some studies have sought to explore if certain organizational configurations are more or less appropriate for certain competitive business strategies (e.g., Kabadayi, Eyuboglu, & Thomas, 2007). Furthermore, Aksin and Masini (2008) identify four configurations of shared service organizations and their relationships with performance.…”
Section: Configuring Qandm Implementation and Industrial Marketingmentioning
confidence: 99%
“…Using the configuration-theoretic approach, some studies have sought to explore if certain organizational configurations are more or less appropriate for certain competitive business strategies (e.g., Kabadayi, Eyuboglu, & Thomas, 2007). Furthermore, Aksin and Masini (2008) identify four configurations of shared service organizations and their relationships with performance.…”
Section: Configuring Qandm Implementation and Industrial Marketingmentioning
confidence: 99%
“…However, to address the gap in the channel implementation literature as discussed by Kabadayi et al , research must provide multichannel guidelines to marketers. 4 The benefi t of using strategy-type theory 5 is that it allows a comprehensive and reputable implementation framework to be used. The Miles and Snow Prospector and Defender theory can be used to determine whether possible solutions to implementation problems raised by respondents apply to all companies using multichannel marketing or only to those following a particular strategy.…”
Section: Original Articlementioning
confidence: 99%
“…6 However, recent researchers have proposed business strategy typologies as a more advanced channel decisionmaking model. Kabadayi et al 4 propose that the role of channels within a multichannel approach is contingent on business strategy. They found that the Porter strategy 14 types, such as Differentiator and Cost Leader, were related to channel strategy characteristics, and that the various multiple channels interact with both strategy and environment in effecting organisational performance.…”
Section: Strategy Implementation Typologiesmentioning
confidence: 99%
See 2 more Smart Citations